Assessment of Knowledge Levels of Nursing and Midwifery Students on Occupational - Fatma Demir; Sibel Yolcu (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: This study was conducted to evaluate the knowledge levels of students studying in nursing and midwifery departments about occupational health and safety. Method: This study is a descriptive study. The population of the research consists of 425 students in the 2nd, 3rd and 4th grades of a foundation university, studying in the "Nursing" department at the School of Nursing and the "Midwifery" department at the Faculty of Health Sciences. No sample selection was made in the research, and the study was conducted between 09.05.2023 and 01.06.2023 among the 2nd, 3rd and 4th grade students (N: 425) of the School of Nursing 'Nursing' and the Faculty of Health Sciences 'Midwifery' department, who met the criteria and accepted the study. Research data were collected online in the Google form environment using the "Student Information Form" and the "Questionnaire on Perceptions of Worker Health and Safety", which measures the level of Occupational Health and Safety knowledge. Results: It was found that 82.2% of the students are studying nursing, while 17.8% are in the midwifery program, and 62% live at home with their families. Approximately 49.6% of the students have good academic performance, while 81% have an average level of knowledge about OHS and 87% have received training related to OHS. The levels of knowledge about OHS among nursing and midwifery students were found to be statistically significant based on age, gender, type of high school graduated from, the class they are studying in, academic performance, knowledge level of OHS, whether they have received Occupational Health and Safety training, and their familiarity with OHS laws. Conclusion: The students' knowledge level on occupational health and safety was found to be good, with a total score of 30.20+-6.79. As a result, students' knowledge should be increased and their courses should be given within the curriculum in order to be in a profession based on practice and to prevent occupational accidents and injuries that may occur.